Trade Policy with Heterogeneous Traders : Do Quotas Get a Bum Rap? - Krishna, Kala (IMF Working Papers; Working Paper, 2007)
This paper considers the effects of trade policy-tariffs and quotas-when importing is done by competitive traders who are identical ex ante but differ ex post. We show that the standard equivalence results no longer hold and the conventional ranking of tariffs and quotas is turned on its head: quotas are not as bad for welfare as previously believed, while tariffs may restrict trade by more than originally intended. Furthermore, the allocation of property rights (quota licenses) has real effects beyond the distribution of rents; this, in turn, has implications for the effects of corruption on welfare.